2018
DOI: 10.1177/0954406218809115
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of the unsteady influence of the inlet guide vanes on cavitation performance of an axial pump

Abstract: The effect of the inlet guide vanes on cavitation performance of an axial pump is investigated to assess the mechanism for cavitation in pumps and improve their cavitation performance. The effect of inlet guide vane angles on cavitation performance was assessed experimentally, and computational fluid dynamics was used to analyze the inner flow field of the axial pump and to probe the cavitation mechanism. The simulation results agree qualitatively with the experimental data, showing that cavitation performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Flow patterns and structures of attached cavitation and vortex cavitation under different conditions were studied by combining visualization with quantitative information [3]. Through visual experiments and numerical simulations, the rotating cavitation flow induced by blade cracking in a high-speed centrifugal pump was investigated, and the influence of inlet blade angle on cavitation performance was evaluated [4,5]. It was found that a positive inlet blade angle improves cavitation performance, while a negative angle suppresses it.…”
Section: Introductionmentioning
confidence: 99%
“…Flow patterns and structures of attached cavitation and vortex cavitation under different conditions were studied by combining visualization with quantitative information [3]. Through visual experiments and numerical simulations, the rotating cavitation flow induced by blade cracking in a high-speed centrifugal pump was investigated, and the influence of inlet blade angle on cavitation performance was evaluated [4,5]. It was found that a positive inlet blade angle improves cavitation performance, while a negative angle suppresses it.…”
Section: Introductionmentioning
confidence: 99%
“…They found a variable called the total vapor fraction to predict critical net positive suction head. Also, many scholars [13][14][15][16][17][18][19][20][21][22] carried out the research on the tip leakage vortex, pressure pulsation, and cavitation mechanism fields in hydraulic machinery and obtained a certain number of achievements, while for studies on energy loss characteristics in hydraulic machinery, an increasing number of scholars use the entropy production method to investigate the loss characteristic accompany with the numerical simulation. Comparing with traditional energy evaluation method, entropy generation analysis method can intuitively and quantitatively determine the position of mechanical energy dissipation in hydraulic machinery; thus, this method is currently applied by some researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the efficiency was most affected by the IGVs. Guo et al [30] found that the installation angle of IGVs had a greater impact on the cavitation of a pump. Yang et al [31] studied the influence of the impeller inlet baffle on its performance.…”
Section: Introductionmentioning
confidence: 99%